Pengaruh Aromaterapi Terhadap Kualitas Tidur, Kualitas Hidup, Kelelahan & Kecemasan Pada Pasien Diabetes Melitus - Mega Ariska; Ida Faridah; Yati Afiyanti (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Diabetes mellitus is an incurable disease but can be controlled by controlling blood sugar levels and improving sleep quality and quality of life in people with diabetes. The prevalence of diabetes mellitus in Banten province has increased in 2013 by 1.3%, while in 2018 it was 2.2%.The purpose of this study is to determine the effectiveness of aromatherapy in patients with diabetes mellitus. Methods: The method used to analyze data is Systematic Literature Review. Search for articles using google scholar database, PubMed, Research Gate, and Elsevier and get eight relevant articles and analyzed using the simplified thematic approach. The article selection process is done using a PRISMA flow diagram. Results: lavender aromatherapy, bitter orange and sandalwood or sandalwood significantly affect changes in sleep quality, quality of life, anxiety and fatigue in patients with type 1 and 2 diabetes mellitus with a combination of massage therapy and foot exercises. Thus, it can be concluded that aromatherapy is effective on sleep quality, quality of life, anxiety and fatigue in patients with type 1 and 2 diabetes mellitus.Conclusion: Therefore, the use of aromatherapy can be recommended as a non-pharmacological intervention that can affect sleep quality in patients with type 2.